Development of a microwave energy delivery system for reversible stunning of cattle. (June 2017) - McLean, D.; Meers, L.; Ralph, J.; Owen, J.S.; Small, A.
Abstract: Stunning prior to slaughter is commonly used to render the animal insensible to pain. However, for certain markets, stunning is disallowed, unless the animal can fully recover if not slaughtered. There are very few available methods of inducing a fully recoverable stun. This paper describes the development of a microwave energy application system for stunning cattle. Cadaver heads were used to demonstrate that brain temperature could be raised to a point at which insensibility would be expected to occur (44 °C), and to calculate the power and time combinations required to achieve this in a range of cattle weights. Surface heating was identified as a cause for potential concern, which was mitigated by the development of another type of microwave applicator. Although the applicator and process variables require validation in animal studies, this technology shows promise as a method of inducing a recoverable stun. Highlights: Application of microwave energy may be a future method of rendering cattle insensible prior to slaughter. Cadaver studies demonstrated that target temperatures can be achieved to induce unconsciousness. The unconsciousness is potentially reversible.